2005
DOI: 10.1017/s1355617705050733
|View full text |Cite
|
Sign up to set email alerts
|

Perceived cognitive dysfunction and observed neuropsychological performance: Longitudinal relation in persons with multiple sclerosis

Abstract: The relation between self-reported cognitive dysfunction and neuropsychological performance over 24 weeks was assessed in a sample of 53 multiple sclerosis patients. Subjects were assessed at Weeks Zero and 24 as part of a clinical trial to enhance cognition. At baseline, subjects had at least mild cognitive impairment on the Rey Auditory Verbal Learning Test and an absence of depression. Neuropsychological performance was assessed with a modification of the well standardized Brief Repeatable Battery. The 5-it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
5
30
0
4
Order By: Relevance
“…Nonetheless, the remainder of null findings confirm the weak association between subjective and objective cognitive performance previously described in the literature. 12,14,15,22 In contrast, reports of cognitive concerns on the PDQ were highly correlated with concomitant reports of depression, anxiety, fatigue, and self-efficacy, in line with existing literature. 15,19,21 Among these variables, reports on the PDQ were most highly correlated with vegetative symptoms of depression (r = 0.60 to 0.66) addition, each index of the PDQ (ie, Attention, Memory, and Planning) maintained significant associations with each self-report factor.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Nonetheless, the remainder of null findings confirm the weak association between subjective and objective cognitive performance previously described in the literature. 12,14,15,22 In contrast, reports of cognitive concerns on the PDQ were highly correlated with concomitant reports of depression, anxiety, fatigue, and self-efficacy, in line with existing literature. 15,19,21 Among these variables, reports on the PDQ were most highly correlated with vegetative symptoms of depression (r = 0.60 to 0.66) addition, each index of the PDQ (ie, Attention, Memory, and Planning) maintained significant associations with each self-report factor.…”
Section: Resultssupporting
confidence: 84%
“…As with the MSNQ, previous investigators have been unable to find a direct and consistent relationship between this measure and objective neuropsychological test performance. 14,15 Reports on the PDQ have similarly been found to be related to concomitant reports of depression. 15 Moreover, in a recent study examining the PDQ in a population of patients with lupus, who tend to underreport cognitive concerns, Vogel et al 16 observed a high correlation between subjective cognitive concerns as measured by the PDQ and self-rated depressive symptoms.…”
mentioning
confidence: 97%
“…While the MSNQ is considered reliable, providing interesting data with regard to indifference and depression pseudo-dementia, 26 several studies show that self-reported scales focusing on cognition are mostly related to depression, not cognitive capacity. 28,29,31 Thus, it would be difficult, if not impossible, to supplant a performance-based measure of cognition with a self-reported assessment, nor to use self-assessments as anchors for interpretability.…”
Section: Self-reports Are Not Valid Anchors For Cognitive Outcomesmentioning
confidence: 99%
“…In a relative short period of testing, the main cognitive domains can be assessed and performances can be compared over a time frame. BRB-N has been normalized and used in Germany 20 , the USA [21][22][23] , Italy 15,24,25 , Spain 26,27 , the Netherlands 28,29 , Israel 30 , Greece 31 , and the United Kingdom 32 . In France, an adapted version of BRB-N has been proposed 33 .…”
Section: Brb-n Is a Neuropsychological Screening Battery Of Tests Thamentioning
confidence: 99%